Tirzepatide modulates gut microbiota homeostasis to protect against diabetic kidney disease - Ma, Jun; Tao, Mengyuan; Zhang, Wencheng; Zhou, Li; Zhang, Henglu; Li, Fei; Zhang, Hongman; Yao, Di; Lu, Weiping; Wang, Min (Frontiers in Molecular Biosciences, 2025)
PurposeThis study evaluated the effect of Tirzepatide on metabolic profiles, kidney function, and gut microbiota composition in mice with diabetic kidney disease (DKD) and clarify the relationship between gut microbiota alterations and the renoprotective effects.MethodsSeven-week-old diabetic db/db mice and db/m controls were randomly assigned to three groups: db/db, db/db-T, and db/m. In the db/db-T group, mice received 10 nmol/kg Tirzepatide injections for a duration of 8 weeks. Biochemical and histopathological analyses were used to assess body weight, blood glucose, lipid profile, hepatic and renal function, and renal histopathological changes in mice. An antibiotic-pretreated group (ABX-db/db-T) was established to explore the impact of gut microbiome depletion on the therapeutic effects of Tirzepatide.The composition of gut microbiota was determined through 16S rRNA gene sequencing to assess microbial differences among groups.ResultsTirzepatide notably decreased fasting blood glucose (FBG), food intake, body weight, glycated hemoglobin A1c (HbA1c), blood lipid levels, and liver function markers, while improving renal function in mice. The renoprotective effects of Tirzepatide were attenuated following gut microbiota depletion. Microbiota analysis revealed that Tirzepatide could reverse dysbiosis and reshape the gut microbial ecosystem. Tirzepatide treatment raised the proportion of beneficial genera, Clostridium_sensu_stricto_1 and Romboutsia, while reducing potentially pathogenic genera, Erysipelatoclostridium and Bacteroides. Moreover, these microbiota changes were significantly correlated with serum creatinine and urinary albumin/creatinine ratio.ConclusionTirzepatide improves renal function and metabolic parameters in DKD mice through gut microbiome regulation. The underlying mechanism involves the modulation of gut–renal axis through the optimization of microbial composition, promoting the development of beneficial bacteria while inhibiting harmful microbes. These results establish a foundational understanding for the use of Tirzepatide in DKD and suggest that combined interventions targeting the gut microbiota may have potential clinical value.